The Influence of Brand Image and Brand Loyalty on Brand Equity on iPhone in iBox Indonesia (Case Study of Instagram Followers @iboxindonesia) - Manalu, Joshua; Susanti, Ety Dwi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Examining how iBox Indonesia customers' perceptions of the brand and their devotion to it affect the value of iPhone goods is the primary goal of this research. This study combined a quantitative approach with an associative research design for its methodology. One hundred individuals who were followers of @iboxindonesia on Instagram were polled to get the data. We used purposive sampling to get this sample. The suggested hypotheses were tested by data analysis utilizing the multiple linear regression approach. The results demonstrate that brand image and loyalty affect iPhone goods' brand equity. This is supported by an F-value of 18. 287, which surpasses the F-table value of 3.089. Some evidence suggests that brand image significantly affects brand equity, while brand loyalty does not seem to have any such effect. Based on these findings, it is clear that attracting consumers requires a concerted effort to boost brand loyalty, even while a favorable brand image — including impressions of great quality and inventive design — contributes to enhancing brand equity. This research offers valuable insights that will help the marketing management of iBox Indonesia develop better strategies to boost the value of their iPhone goods. Also included are suggestions for future studies, such as looking at other variables that might influence customer loyalty to a business.